Soliton spectrum of integrable models with local symmetries - Gomes, Jose F. [UNESP]; Gueuvoghlanian, Emilia P.; Sotkov, Galen M. [UNESP]; Zimerman, Abraham H. [UNESP] (Springer Nature, 2002)
The soliton spectrum (massive and massless) of a family of integrable models with local U(1) and U(1) ⊗U(1) symmetries is studied. These models represent relevant integrable deformations of SL(2,ℝ) ⊗U(1) n-1-WZW and SL(2,ℝ) ⊗ SL(2,ℝ) ⊗U(1) n-2-WZW models. Their massless solitons appear as specific topological solutions of the U(1)(or U(1) ⊗ U(1)-) CFTs. The nonconformal analog of the GKO-coset formula is derived and used in the construction of the composite massive solitons of the ungauged integrable models. © SISSA/ISAS 2002.
Keywords: Conformal and W Symmetry; Integrable Field Theories; Integrable Hierarchies; Solitons Monopoles and Instantons